2022
DOI: 10.3390/biomedicines10092302
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Differences in Pain and Opioid Use Disorder Management: A Cross-Sectional Real-World Study

Abstract: (1) Background: It is essential to focus attention on sex-specific factors which are clinically relevant in pain management, especially with regards to opioid use disorder (OUD) risk. The aim of this study was to explore potential sex-differences in chronic non-cancer pain (CNCP) outpatients. (2) Methods: An observational cross-sectional study was conducted under CNCP outpatients with long-term prescribed opioids (n = 806), wherein 137 patients had an OUD diagnosis (cases, 64% females) and 669 did not (control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Furthermore, recent data from our region showed that younger patients, those with a lower employment status, those taking high opioid doses and on psychotropic co‐prescription were more vulnerable to OUD 40 . Thus, prevention and treatment programs should be tailored to consider sex and age differences in sources of opioids 41 as obtained from physicians, drug dealers or friends/relatives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, recent data from our region showed that younger patients, those with a lower employment status, those taking high opioid doses and on psychotropic co‐prescription were more vulnerable to OUD 40 . Thus, prevention and treatment programs should be tailored to consider sex and age differences in sources of opioids 41 as obtained from physicians, drug dealers or friends/relatives.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent data from our region showed that younger patients, those with a lower employment status, those taking high opioid doses and on psychotropic co-prescription were more vulnerable to OUD. 40 Thus, prevention and treatment programs should be tailored to consider sex and age differences in sources of opioids 41 as obtained from physicians, drug dealers or friends/relatives. Incident opioid overdoses have also been related to lower socio-economic status (due to completed level of education and having benefited from T A B L E 2 Associations between OPRM1 DNA methylation (CpG sites 1-5) and clinical outcomes in terms of effectiveness and tolerability as adverse events (AEs) due to the regression model results.…”
Section: Discussionmentioning
confidence: 99%
“…These results may provide a reference for clinicians to use alfentanil in painless bronchoscopy with no need to consider the influence of gender factors. As animal and human studies have suggested that there existed gender differences in opioid-induced analgesia and associated adverse events (2)(3)(4)(5), clinicians need to be aware of the gender differences when administering opioids (6). The authors have studied a very interesting topic and provided novel evidence on this matter, though more investigations are needed to confirm the results.…”
mentioning
confidence: 99%
“…Sex disparities were shown to be associated with higher hospital resources and worse drug acceptability in female OXN users. Also, Escorial and colleagues investigated the possible sex-related disparities among outpatients with CNCP, with an observational cross-sectional study on 806 patients [47]. Of these patients, 137 had an opioid use disorder diagnosis; the other 669 were considered as the control group.…”
mentioning
confidence: 99%